A PETROLOGIC, GEOCHEMICAL AND OSMIUM ISOTOPIC STUDY OF SELECTED PRECAMBRIAN KOMATIITES - Gangopadhyay, Amitava (2004)
The major and trace elements, and Re-Os isotope systematics of the ca. 2.7-Ga komatiites from the Alexo and Dundonald Beach areas in the Abitibi greenstone belt, Canada, and ca. 2.0-Ga komatiites from Jeesiörova, Finnish Lapland were examined in order to constrain the long-term Os isotopic evolution of their mantle sources and also to evaluate different petrogenetic models for their generation. The Re-Os isotope results for whole-rock komatiites and chromite separates from Alexo, Dundonald Beach and the Jeesiörova areas, all yield precisely chondritic intial Os isotopic compositions of their mantle sources (gamma-Os = -0.1± 1.0, 0.0 ± 0.6 and 0.1± 0.5, respectively), consistent with that for the projected primitive upper mantle. The uniform chondritic initial Os isotopic compositions of these komatiites suggest their derivation from mantle sources that had undergone neither long-term Re-depletion nor enrichments in radiogenic Os-187. The uniform chondritic initial Os isotopic compositions of the Ti-rich Finnish komatiites also suggest that the processes responsible for high Ti concentrations in the Finnish rocks must have either been coeval with the generation of the rocks or Re and Os were not significantly fractionated during the processes. The uniform Os isotopic compositions of the Precambrian mantle source regions for these komatiites are in contrast to the variably radiogenic Os isotopic compositions, commonly reported for the present-day ocean island basalts and modern arc-related rocks. This suggests that the Precambrian mantle was significantly more homogeneous than the present-day mantle. Finally, the high-precision Os isotopic results of this study, combined with those previously published for Precambrian ultramafic rocks suggest that although Os isotopic heterogeneities began to appear in the terrestrial mantle as early as ~2.8 Ga, large portions of the Precambrian mantle were evidently not affected by the processes responsible for long-term Os isotopic heterogeneities.